Indoor air quality inside a new air-conditioning building - Omar Ahmad Mohamed Noh. (2010)
New building has been associated with the presence of new carpets and upholsteries, new electronics and other plastics equipments, glues and adhesives and aerosols which may produce indoor air pollutants. This project is to find out whether the above potential pollutants emitter are true. Parameters such as temperature, relative humidity, carbon dioxide, carbon monoxide, ozone, hydrocarbons, bacteria and fungi, particulate matter concentrations will be measured and evaluated. This project is crucial in determining whether the room is healthy or is it showing signs of a sick building syndrome.